Identification of Defective Joints in Beams via Torsional Vibration - Mostafa Kohantorabi; Alireza Asgari; Mona Shayestehkia; Mobina Kohantorabi (Drvna Industrija, 2022)
The determination of the shear dynamic modulus in wood product panels is of greater importance than its determination in wood beams. Yet with regards to the effect of defects on the obtained values of shear modulus, this factor is used to detect the defects and the degree of the defects. In this study, the effect of gluing defects in two joint shapes (scarf (45°) and finger joints (10 mm length and 3 mm pitch) were evaluated non-destructively using the torsional vibration method. Rectangular wood specimens with dimensions of 20 mm × 40 mm × 360 mm (R × T × L) were prepared from clear eastern beech. The joints were located at similar positions in the middle of the beams. The results showed that creating a healthy joint did not significantly change the values obtained for the shear modulus in either of the joint shapes. However, reducing the adhesion level in both types of joints caused a significant reduction in the shear modulus values. The results show that the changes in the dynamic shear modulus values in both joint types, as a result of changes in the glue coverage rating (fully, medium and low-glued joints) allows the detection of the defects as well as the degree of the defects.